2023
DOI: 10.1039/d3cs00627a
|View full text |Cite
|
Sign up to set email alerts
|

Single atom catalyst-mediated generation of reactive species in water treatment

Virender K. Sharma,
Xingmao Ma,
Radek Zboril

Abstract: Unique activation mechanisms of oxidants by metal single atom catalysts for water treatment were compared with conventional advanced oxidation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…In addition, SO 4 c − is predominantly generated from two types of persulfate oxidants (PDS and PMS), which can cleave O-O bonds through either energy transfer or reductive electron transfer (i.e., Fenton-like reactions) to oxidize target pollutants in wastewater (eqn (4)-( 6)). 11,168,169 During the Fenton-like reaction, single metal atoms (hM n+ ) serve as the catalytic active sites, binding to persulfate and undergoing oxidation to form hM (n+1)+ through one-electron transfer, thereby generating reactive radicals (SO 4 c − and $OH). Subsequently, upon detachment of surface-bound SO 4 2− and OH − , hM (n+1)+ can be further reduced to hM n+ by persulfate, thus completing the redox cycle (Fig.…”
Section: Radical Pathways and The Associated Active Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, SO 4 c − is predominantly generated from two types of persulfate oxidants (PDS and PMS), which can cleave O-O bonds through either energy transfer or reductive electron transfer (i.e., Fenton-like reactions) to oxidize target pollutants in wastewater (eqn (4)-( 6)). 11,168,169 During the Fenton-like reaction, single metal atoms (hM n+ ) serve as the catalytic active sites, binding to persulfate and undergoing oxidation to form hM (n+1)+ through one-electron transfer, thereby generating reactive radicals (SO 4 c − and $OH). Subsequently, upon detachment of surface-bound SO 4 2− and OH − , hM (n+1)+ can be further reduced to hM n+ by persulfate, thus completing the redox cycle (Fig.…”
Section: Radical Pathways and The Associated Active Sitesmentioning
confidence: 99%
“…The HVMO pathway has been systematically investigated in SAC-based Fenton-like reactions. 168,170 Compared with SO 4 c − and $OH, the HVMO species Fe(IV)-oxo (E 0 = 2.0 V) is a milder oxidant, but its lifetime can last up to 0.1 s, becoming the suitable ROS for oxidizing target ECs in the complicated water…”
Section: Nonradical Pathways and The Associated Active Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, metal-based advanced oxidation processes (AOPs) are a group of emerging oxidation technologies that attract substantial research due to their high efficiency in degrading micropollutants. Metal-based AOPs apply aqueous metal ions, metal-containing minerals, or single metal atom catalysts to activate oxidants and generate highly reactive high-valent metals or nonmetal radicals. The metal activators may react with the oxidants through either single electron transfer (SET) or double electron transfer (DET). The SET reactions lead to the formation of both high-valent metal species and radicals, while DET reactions are usually based on oxygen atom transfer (OAT) from oxidants to metals and generate only high-valent metals as the reactive species.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al reported the successful preparation of an ECL biosensing platform based on luminol-H 2 O 2 –Fe–N-C SACs, combined with the specific recognition of antigen–antibody to accomplish the sensitive detection of carcinoembryonic antigen with a limit of detection of 1.1 pg mL –1 . Additionally, many studies have shown that central metal atoms always act as actual catalytic active sites. , Therefore, selecting the proper center metal atoms is considered a straightforward and efficient strategy to regulate the internal catalytic activity of SACs. A variety of Cu-related single-atom materials , have been studied and found to have excellent catalytic activity, while their enzyme-like activity has also been extensively investigated. Moreover, the chemical stability and cost-efficiency of polymeric carbon nitride (CN) make it a highly regarded substrate material for single-atom dispersion.…”
Section: Introductionmentioning
confidence: 99%